Comparative Analysis of Endocarditis in Congenital Heart Disease Patients Across Age Groups: Endocarditis in Congenital Heart Disease Patients Across Age Groups - Naeem, Muhammad; Rehman, Fazal Ur; Shafiq, Umar; Munir, Ussama; Zafar, Muhammad Adnan; Ahmad, Iftikhar (Pakistan Journal of Health Sciences, 2025)
Infective endocarditis remains a serious complication in patients with congenital heart disease, yet age-related differences in presentation and outcomes are not well understood. Objectives: To evaluate age-stratified clinical characteristics, microbiological profiles, and in-hospital outcomes of infective endocarditis (IE) in patients with congenital heart disease (CHD), with emphasis on diagnostic patterns and mortality predictors. Methods: This cross-sectional analytical study was conducted at the Department of Cardiology, Quaid-e-Azam Medical College, Bahawalpur, from March 2024 to March 2025. A total of 113 patients with CHD and definite IE, diagnosed per modified Duke criteria, were enrolled through non-probability consecutive sampling. Patients were stratified into two groups: ≤18 years (n=57) and >18 years (n=56). Data on demographics, clinical variables, blood culture results, inflammatory markers, echocardiographic findings, and in-hospital outcomes were collected. Results: Septal defects were significantly more common in children (61.4%) versus adults (p=0.0288). Adults exhibited higher mean creatinine (1.21±0.42 mg/dL vs 0.96 ± 0.28 mg/dL, p=0.032) and vegetation size (10.4 ± 4.2 mm vs 8.6 ±2 .9 mm, p=0.031). In-hospital mortality was 12.4%. Vegetation size >10 mm and prosthetic material presence were significant mortality predictors (adjusted OR=4.23, 95% CI: 1.63–10.99, p=0.001; and OR=3.45, 95% CI: 1.19–9.83, p=0.009). Blood culture positivity reduced mortality risk (adjusted OR=0.53, 95% CI: 0.22–0.91, p=0.001). Conclusions: Adult CHD patients with IE presented with more advanced disease and higher mortality risk, especially with prosthetic material and large vegetations.